2014
DOI: 10.1039/c3sm53229a
|View full text |Cite
|
Sign up to set email alerts
|

Using THz time-scale infrared spectroscopy to examine the role of collective, thermal fluctuations in the formation of myoglobin allosteric communication pathways and ligand specificity

Abstract: In this investigation we use THz time-scale spectroscopy to conduct an initial set of studies on myoglobin with the aim of providing further insight into the global, collective thermal fluctuations in the protein that have been hypothesized to play a prominent role in the dynamic formation of transient ligand channels as well as in shaping the molecular level basis for ligand discrimination. Using the two ligands O2 and CO, we have determined that the perturbation from the heme-ligand complex has a strong infl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 70 publications
1
15
0
Order By: Relevance
“…Below the glass transition temperature, the LHS spectrum also exhibits prominent peaks at approximately 50, 40, and 25 cm −1 in the low-frequency spectral region. The 50 cm −1 and 40 cm −1 modes are likely delocalized backbone torsions that are directly intertwined with the fast water dynamics taking place in the protein hydration shell [31],[33], while the ~25 cm −1 mode in the LHS spectrum is close in frequency to the reported boson peak from other investigations [34]-–[38] on protein glassy dynamics. Additionally, a solvent-induced dispersive mode has been identified in THz time scale scattering measurements in globular proteins [14],[39] at a similar frequency (~25 cm −1 ).…”
Section: Resultssupporting
confidence: 55%
See 1 more Smart Citation
“…Below the glass transition temperature, the LHS spectrum also exhibits prominent peaks at approximately 50, 40, and 25 cm −1 in the low-frequency spectral region. The 50 cm −1 and 40 cm −1 modes are likely delocalized backbone torsions that are directly intertwined with the fast water dynamics taking place in the protein hydration shell [31],[33], while the ~25 cm −1 mode in the LHS spectrum is close in frequency to the reported boson peak from other investigations [34]-–[38] on protein glassy dynamics. Additionally, a solvent-induced dispersive mode has been identified in THz time scale scattering measurements in globular proteins [14],[39] at a similar frequency (~25 cm −1 ).…”
Section: Resultssupporting
confidence: 55%
“…At first glance, the HHS spectrum in Figure 1a appears to contain only one large, major peak centered at about 60 cm −1 . Based on the peak’s temperature dependence and previous investigations on globular proteins [31],[32], we initially speculate that ~60 cm −1 centered mode stems from localized, internal side-chain fluctuations that are indirectly connected with the hydration water dynamics on the picosecond time scale. In the LHS spectrum (Figure 1b), we identify a similar type of side chain fluctuation at about 90 cm −1 .…”
Section: Resultsmentioning
confidence: 89%
“…Hence, the vibrational analyses from the MD simulations carried out in this investigation combined with our previous studies on other proteins allow us to associate the experimentally observed peaks at about 120 cm −1 and 130 cm −1 in Fig. 4a with anharmonic, solvent-mediated fluctuations that couple to protein main-chain and backbone atoms, respectively485256. It is interesting to note that both solvent-mediated modes oscillate distinctly from the solvent-induced modes observed in the experimental dark-state spectrum.…”
Section: Resultsmentioning
confidence: 58%
“…It forms links between a number of different network communities. In general, highly coevolved residues that serve as “linkers” between different network communities like Asn302 have been shown to facilitate enhanced long-range signaling in the network of connected residues5671. It has been proposed that through these linker residues a signaling pathway is modified when a perturbation is introduced.…”
Section: Resultsmentioning
confidence: 99%
“…However,d ue to the extended timescales neededf or the modelling of the diffusion process, it was the advent of GPU-accelerated MD simulations techniques which boostedr esearch in this field yielding reasonable rate constants for ligand diffusion to myoglobin, [15][16][17][18][19][20][21] and to nitrogenase/ hydrogenasee nzymes. Ligand diffusion and the internal motions of the protein have been stud-ied using molecular dynamics simulations in which the whole protein structure, the ligand molecules andt he surrounding solventc an be explicitly described.…”
Section: Introductionmentioning
confidence: 99%